Tháng Ba 1, 2024

Chọn đáp án không đúng:

Chọn đáp án không đúng:

A. \(\frac{x-3}{{{x}^{2}}-9}=\frac{1}{x+3}\)

B. \(\frac{5x+5}{5x}=\frac{x+1}{x}\)

C. \(\frac{{{x}^{2}}-6x+9}{9-{{x}^{2}}}=\frac{3-x}{x+3}\)

D. \(\frac{x({{x}^{2}}-4)}{2-x}=x(x+2)\)

Hướng dẫn Chọn đáp án là: D

Lời giải chi tiết:

+) Đáp án A: \(\frac{x-3}{{{x}^{2}}-9}=\frac{x-3}{\left( x-3 \right)\left( x+3 \right)}=\frac{1}{x+3}\Rightarrow \) A đúng.

+) Đáp án B: \(\frac{5x+5}{5x}=\frac{5\left( x+1 \right)}{5x}=\frac{x+1}{x}\Rightarrow \) B đúng.

+) Đáp án C: \(\frac{{{x}^{2}}-6x+9}{9-{{x}^{2}}}=\frac{{{\left( 3-x \right)}^{2}}}{\left( 3-x \right)\left( 3+x \right)}=\frac{3-x}{x+3}\Rightarrow \) C đúng.

+) Đáp án D: \(\frac{x({{x}^{2}}-4)}{2-x}=\frac{x(x-2)(x+2)}{-(x-2)}=-x(x+2)\Rightarrow \) D sai.

Chọn D.